2022
DOI: 10.1186/s13071-022-05585-0
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis in the Ntui Health District of Cameroon: epidemiological, entomological and parasitological findings in relation to elimination prospects

Abstract: Background Despite decades of community-directed treatment with ivermectin (CDTI), onchocerciasis transmission persists in Cameroon and has been associated with increased risk for epilepsy in endemic communities. We investigated the onchocerciasis situation in the Ntui Health District (a known onchocerciasis focus in Cameroon where the Sanaga River constitutes the main source of black fly vectors) using parasitological, entomological and serological parameters. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…The 50.9% therapeutic coverage of the 2021 CDTI session in our study population, similar to the 54.2% coverage obtained in these same villages without using a door-to-door approach [ 25 ], falls way below the optimal threshold of 85% needed to rapidly achieve onchocerciasis elimination [ 34 ]. This may be indicative of regular sub-optimal coverage rates over the years, explaining why onchocerciasis transmission persists in these villages despite more than two decades of annual mass treatment with ivermectin.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The 50.9% therapeutic coverage of the 2021 CDTI session in our study population, similar to the 54.2% coverage obtained in these same villages without using a door-to-door approach [ 25 ], falls way below the optimal threshold of 85% needed to rapidly achieve onchocerciasis elimination [ 34 ]. This may be indicative of regular sub-optimal coverage rates over the years, explaining why onchocerciasis transmission persists in these villages despite more than two decades of annual mass treatment with ivermectin.…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with previous findings from endemic communities in the Mbam valley in Cameroon where only one case of Nakalanga syndrome was found after surveying five villages [ 30 ], suggesting that although onchocerciasis transmission persists in Cameroonian communities, the infectious context (for instance: O. volvulus parasitic levels and chronicity of infection) may be enough just to trigger seizures, but not suffice to induce Nakalanga features in the affected individuals. Indeed, the reported community microfilarial loads in our study sites are rather low (values below 2 were reported [ 25 ]), supporting ongoing onchocerciasis transmission but with few parasites in circulation.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The gathering took place from 7:00 AM to 6:00 PM over three consecutive days in July 2021. Nachtigal is a rural community of the Ntui Health District, an onchocerciasis-endemic area with a high prevalence of OAE (Siewe Fodjo et al . 2022), in the forest-savannah transition zone in the Centre Region of Cameroon.…”
Section: Methodsmentioning
confidence: 99%